2001
DOI: 10.1097/00006231-200111000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Reverse redistribution of 99mTc-sestamibi after direct percutaneous transluminal coronary angioplasty in acute myocardial infarction: relationship with wall motion and functional response to dobutamine stimulation

Abstract: Reverse redistribution (RR) of 99mTc-sestamibi is observed after direct percutaneous transluminal coronary angioplasty (PTCA) in acute myocardial infarction (AMI). The purpose of this study was to clarify the functional characteristics of myocardial segments with RR after direct PTCA in AMI. Thirty patients with AMI who had undergone direct PTCA were examined. Myocardial perfusion tomography with 99mTc-sestamibi and low dose dobutamine echocardiography were performed within 2 weeks of the onset. The 99mTc-sest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…However, in recent years, several studies have reported the presence of RRD in salvaged myocardium in at-risk areas in patients with AMI who underwent direct PCI [14][15][16][17][18][19][20][21]. Sugihara et al [14] reported that the frequency of observed RRD of 99m Tctetrofosmin was significantly higher in patients who underwent reperfusion therapy than in those who did not in the sub-acute phase of AMI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in recent years, several studies have reported the presence of RRD in salvaged myocardium in at-risk areas in patients with AMI who underwent direct PCI [14][15][16][17][18][19][20][21]. Sugihara et al [14] reported that the frequency of observed RRD of 99m Tctetrofosmin was significantly higher in patients who underwent reperfusion therapy than in those who did not in the sub-acute phase of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse redistribution (RRD) was observed between the initial and delayed images of AMI on myocardial perfusion images using a 99m Tc-labeled agent with almost no clearance in normal myocardium, which is reported to reflect mitochondrial damage in myocardium [14][15][16][17]. It has also been reported that RRD can predict functional recovery in the chronic phase.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, 99m Tc-labeled agents are widely used as myocardial perfusion tracers [17][18][19][20][21][22]. However, washout phenomenon (WO) of the 99m Tclabeled agents from early imaging to delayed imaging has been reported observed in various diseases such as acute myocardial infarction (AMI), complete left bundle branch block, and hypertrophic cardiomyopathy (HCM) [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%